Initial characterization of human DHRS1 (SDR19C1), a member of the short-chain dehydrogenase/reductase superfamily. Issue 185 (January 2019) - Zemanová, Lucie; Navrátilová, Hana; Andrýs, Rudolf; Šperková, Kristýna; Andrejs, Jiří; Kozáková, Klára; Meier, Marc; Möller, Gabriele; Novotná, Eva; Šafr, Miroslav; Adamski, Jerzy; Wsól, Vladimír
Highlights: DHRS1 is a monotopic membrane protein from the endoplasmic reticulum. DHRS1 is an NADPH-dependent reductase of steroid hormones and xenobiotics. DHRS1 expression patterns were determined at both the mRNA and the protein levels. Abstract: Many enzymes from the short-chain dehydrogenase/reductase superfamily (SDR) have already been well characterized, particularly those that participate in crucial biochemical reactions in the human body ( e.g. 11β-hydroxysteroid dehydrogenase 1, 17β-hydroxysteroid dehydrogenase 1 or carbonyl reductase 1). Several other SDR enzymes are completely or almost completely uncharacterized, such as DHRS1 (also known as SDR19C1). Based on our in silico and experimental approaches, DHRS1 is described as a likely monotopic protein that interacts with the membrane of the endoplasmic reticulum. The highest expression level of DHRS1 protein was observed in human liver and adrenals. The recombinant form of DHRS1 was purified using the detergent n-dodecyl-β-D-maltoside, and DHRS1 was proven to be an NADPH-dependent reductase that is able to catalyse the in vitro reductive conversion of some steroids (estrone, androstene-3, 17-dione and cortisone), as well as other endogenous substances and xenobiotics. The expression pattern and enzyme activities fit to a role in steroid and/or xenobiotic metabolism; however, more research is needed to fully clarify the exact biological function of DHRS1.